Effects of high-fat diet on plasma profiles of eicosanoid metabolites in mice - Wang, Weicang (Prostaglandins Other Lipid Mediat, 2016)
Obesity is a serious health problem in the US and is associated with increased risks of various human diseases. To date, the mechanisms by which obesity increases the risks of a wide range of human diseases are not well understood. Here we used a LC–MS/MS-based lipidomics, which can analyze >100 bioactive lipid mediators produced by cyclooxygenase, lipoxygenase, and cytochrome P450 enzymes, to analyze plasma profiles of lipid mediators in high-fat diet induced obesity in C57BL/6 mice. Our results show that the plasma concentrations of epoxyoctadecenoic acids (EpOMEs, also termed as leukotoxins) are significantly increased in plasma of high-fat diet-fed mice, in addition, EpOMEs are among the most abundant lipid mediators detected in mouse plasma. Since substantial studies have shown that EpOMEs and their metabolites have a large array of detrimental effects on health, enhanced levels of EpOMEs could contribute to the pathology of obesity